Measures To Prevent Myopia Among Adolescents - Rasulova Nilufar; Azamatova Fazilat (Genius Journals, 2024)
Myopia, or nearsightedness, has become a global public health concern, especially among adolescents. The increasing prevalence of myopia in younger populations is largely attributed to lifestyle changes, including prolonged screen time, limited outdoor activity, and high educational pressures. If left unmanaged, progressive myopia can lead to severe complications, including retinal detachment, glaucoma, and vision loss. This article explores the causes, contributing factors, and preventive strategies for myopia in adolescents. A comprehensive approach combining behavioral changes, environmental modifications, and medical interventions is essential to mitigate its impact. Strategies like promoting outdoor activities, reducing screen time, and regular eye examinations are crucial. Additionally, advances in optical and pharmacological treatments, such as myopia control lenses and atropine eye drops, are discussed. The paper emphasizes the importance of early intervention and awareness campaigns in curbing the myopia epidemic.
Keywords: Myopia; adolescents; preventive measures